Can Course Design and Language Competence Contribute to the Understanding of Literature for EFL Students? A Case Study at a Saudi Arabian University - AbdelFattah, Rabab Ahmed Amin (Journal of English Teaching and Learning Issues, 2024)
Teaching literature without a prerequisite in a Saudi Arabian University curriculum for EFL students revealed a variety of impediments, including a lack of critical and analytical skills, ambiguity tolerance issues, and a low level of English proficiency. This research aims to examine the course limitations and assessments and provide a development strategy to improve those key skills. As a result, the study separated the topic into numerous questions that constitute the primary axes the research aims to address. The first question is whether the existing course design, ENG280 Introduction to Literature, is appropriate for level 4 students. The second question concerns whether a prerequisite should be included in the academic plan. The final question concerns how students' English proficiency affects their understanding of the course. Methodological triangulation is used to address these questions appropriately. The utilization of both qualitative and quantitative data collection methods provides the availability of high-quality data required to improve the findings. The data was collected using a lecturer's questionnaire and an English language competence test. The language competence test is aligned with the 2020 edition of the Common European Framework of References for Languages (CEFR). The study highlighted flaws in the course design and assessments, including advanced skill expectations that were inappropriate for fourth-level students' linguistic and skill capabilities. As a result, the study provides developmental suggestions for course design and assessments that can successfully address issues connected to students' linguistic and literary abilities. Implementing the improvement plan will simultaneously enhance the students’ linguistic level and develop their critical analysis abilities. Students will also have sufficient time and diverse assessment methods that align with their linguistic and literary capabilities, providing them with encouragement and motivation to learn.